Postpartum anemia and its determinant factors among postnatal women in two selected health institutes in Gondar, Northwest Ethiopia: A facility-based, cross-sectional study - Bambo, Getachew Mesfin; Kebede, Samuel Sahile; Sitotaw, Chomaw; Shiferaw, Elias; Melku, Mulugeta (Frontiers in Medicine, 2023)
Background: Anemia is highly prevalent globally and disproportionately affecting postnatal women in association with socioeconomy, obstetric, clinical and dietary characteristic of women. It is a significant cause of maternal mortality and morbidity on a global scale. Objective: The main aim this study was to determine the magnitude of postpartum anemia and associated factors among postnatal women in two selected health facilities in Gondar town, northwest Ethiopia. Methods: A facility-based cross-sectional study was conducted among 282 postnatal women from March to May 2021. Systematic sampling technique was applied to recruit study participants from each institute. Sociodemographic, obstetric and clinical data were collected by semi-structured questionnaire. A venous blood sample was collected to determine the red blood cell parameters. Thin blood smear preparation was done to examine blood morphology. In addition, direct wet mount and formalin-ether sedimentation technique were used for stool examination for identification of intestinal parasites. Data were entered in EpiData version 4.6.0.0 and exported to Stata version 14.0 for statistical analysis. Descriptive statistics were presented in texts, tables and figures. Binary logistic regression model was used to identify risk factors of postpartum anemia. P-value < 0.05 was considered as statistically significant. Results: The proportion of postpartum anemia was 47.16%; 95% CI; 41.30-53.03 with moderate mild and severe anemia accounting for 45.11%, 42.86% and 12.03%, respectively. The majority of anemia (94%) was normocytic normochromic type. It was associated with postpartum hemorrhage (AOR = 2.23; 95% CI: 1.24-4.01), cesarean section (AOR = 4.10; 95% CI: 2.11-7.78), lack of iron and folate supplementation during pregnancy (AOR = 2.12; 95% CI: 1.17-4.02) and low diet diversity level (AOR = 1.83; 95% CI: 1.05-3.18). Conclusion: The prevalence of postpartum anemia was a major public health concerns. The magnitude of postpartum anemia can be reduced by taking iron and folate supplements, improved maternal health care and diet diversity during pregnancy and postpartum. Therefore, identified factors should be considered to prevent and control postpartum anemia.